2004
DOI: 10.1128/cmr.17.1.72-97.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium Taxonomy: Recent Advances and Implications for Public Health

Abstract: There has been an explosion of descriptions of new species of Cryptosporidium during the last two decades. This has been accompanied by confusion regarding the criteria for species designation, largely because of the lack of distinct morphologic differences and strict host specificity among Cryptosporidium spp. A review of the biologic species concept, the International Code of Zoological Nomenclature (ICZN), and current practices for Cryptosporidium species designation calls for the establishment of guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
523
4
60

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 774 publications
(636 citation statements)
references
References 223 publications
18
523
4
60
Order By: Relevance
“…Oocysts of C. baileyi were inoculated orally into several animals to determine its host specificity. Mice and goats inoculated with C. baileyi oocysts did not become infected Xiao et al, 2004). Based on these theories and hence the detected Cryptosporidium oocysts in the examined young buffalo calf feces stained with Ziehl-Neelsen technique were morphologically similar to C. parvum oocysts.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Oocysts of C. baileyi were inoculated orally into several animals to determine its host specificity. Mice and goats inoculated with C. baileyi oocysts did not become infected Xiao et al, 2004). Based on these theories and hence the detected Cryptosporidium oocysts in the examined young buffalo calf feces stained with Ziehl-Neelsen technique were morphologically similar to C. parvum oocysts.…”
Section: Discussionmentioning
confidence: 67%
“…Parasitol., 10 (4): 127-141, 2015 In accordance, during the present study, 823 bp fragments amplified from the 18S SSU rRNA gene could be noted after nested PCR reaction from buffalo's feces. Previous studies indicated the usefulness of the small subunit (SSU) ribosomal RNA genes as genetic markers for the specific identification of Cryptosporidium having relatively low intraspecific and relatively high interspecific sequence variation (Fayer et al, 2000;Xiao et al, 2004;Jex et al, 2007). Thus, they had been utilized in systematic (phylogenetic) investigations of Cryptosporidium providing the basis for the current classification of members within the genus (Morgan et al, 1999a;Xiao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e Cryptosporidium spp. pela dificuldade de distinção de organismos espécie-específicos (Ramirez et al, 2004;Xiao et al, 2004).…”
Section: Introductionunclassified